HUBUNGAN KETERAMPILAN MENYIMAK CERITA PADA ANAK USIA DINI DENGAN PENGGUNAAN MEDIA ANIMASI AUDIO VISUAL DALAM PEMBELAJARAN DI KB. AT-TAQWA TAHUN PELAJARN 2021/2022 - Putri Mustiningtyas; Wahono Wahono; Naili Sa’ida (Universitas Muhammadiyah Surabaya, 2022)
The purpose of this study was to determine the relationship between story listening skills in early childhood with the use of audio visual animation media in learning at Kb. At-Taqwa Academic Year 2021/2022. At the beginning of human life first learn to listen, then speak, read, and write. Mastery of listening skills will affect other language skills. The research method used in this research is descriptive qualitative. With data collection techniques by observation, interviews, documentaries and questionnaires. In this study to analyze the data the author uses statistical analysis (statistical analysis). The results obtained in this study are the relationship between story listening skills in early childhood and the use of audio-visual animation media in learning at At-taqwa Kindergarten in the 2021/2022 academic year. In the context of learning effectiveness, the main thing is listening to stories later in family planning activities. At-Taqwa is expected to apply more audio- visual animation learning so that it can improve the intelligence of students in family planning. At- Taqwa.Â Keywords: statistical analysis; interview; audio visual; questionnaire